Putusan Kasasi Mahkamah Agung Nomor 2704 K/PDT/2015 Tentang Sewa Menyewa: Analisis Yuridis dan Aspek Keadilan - Rais, Muslihin (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to analyze the legal considerations of the Supreme Court in the decision Number 2704 k/Pdt/2015 Regarding Leasing and whether the Supreme Court's verdict in the case is in accordance with the laws and regulations, and the value of legal justice. This research utilized the juridical-normative research method with a statutory approach and a conceptual approach. The primary legal materials and secondary legal materials that have been collected are then grouped and reviewed based on the legislative and conceptual approaches. The results of this study indicate: 1.) Legal considerations of the Supreme Court in the a quo ruling deciding to reject the petition of cassation applicants is to assess the basis and legal reasons, where the legal grounds and reasons refer to the sale and purchase agreement deed and the lease agreement. 2). Conformity of the a quo decision against legislation and invitation and the value of justice can be seen from the suitability of the application of the rules, which have been appropriate because it refers to Law Number 48 of 2009 concerning Judicial Power, Law Number 3 of 2009 concerning the Supreme Court, and related to sale and purchase and rent leases refer to the Sale and Purchase Deed and the lease deed.AbstrakPutusan Nomor 2704 K/Pdt/2015 tentang Sewa Menyewa dan apakah putusan Mahkamah Agung dalam kasus tersebut telah sesuai dengan peraturan perundang-undangan dan nilai keadilan hukum. Penelitian ini menggunakan metode penelitian yuridis-normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Bahan hukum primer dan bahan hukum sekunder yang telah dikumpulkan tersebut kemudian dikelompokkan dan dikaji berdasarkan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian ini menunjukkan: 1). Pertimbangan hukum Mahkamah Agung dalam putusan a quo yang memutuskan untuk menolak permohonan pemohon kasasi adalah dengan menilai dasar dan alasan hukumnya, di mana dasar dan alasan hukumnya mengacu pada akta perjanjian jual beli dan akta perjanjian sewa menyewa. 2). Kesesuaian putusan a quo terhadap peraturan perundangan-undangan dan nilai keadilan dapat dilihat dari kesesuaian penerapan aturannya, yang telah sesuai karena mengacu pada Undang-Undang Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman, Undang-Undang Nomor 3 Tahun 2009 tentang Mahkamah Agung, dan jual beli dan sewa menyewanya mengacu pada akta jual beli dan akta sewa menyewa.